Assortative mate preferences for height across short-term and long-term relationship contexts in a cross-cultural sample - Pisanski, Katarzyna; Fernandez-Alonso, Maydel; Díaz-Simón, Nadir; Oleszkiewicz, Anna; Sardinas, Adrian; Pellegrino, Robert; Estevez, Nancy; Mora, Emanuel C.; Luckett, Curtis R.; Feinberg, David R. (Frontiers in Psychology, 2022)
Height preferences reflecting positive assortative mating for height – wherein an individual’s own height positively predicts the preferred height of their mate – have been observed in several distinct human populations and are thought to increase reproductive fitness. However, the extent to which assortative preferences for height differ strategically for short-term versus long-term relationship partners, as they do for numerous other indices of mate quality, remains unclear. We explore this possibility in a large representative sample of over 500 men and women aged 15-77 from Canada, Cuba, Norway and the United States. Participants’ own heights were measured, and they indicated their height preferences for a long-term and short-term mate using graphic stimuli containing metric indices. Replicating the “male-taller norm”, participants on average preferred taller-than-average male mates, and shorter-than-average female mates. Positive assortative preferences for height were observed across sexes and samples, however the strength of these height preferences varied with relationship context for men, and not for women. Taller men preferred relatively shorter women for short-term relationships than for long-term relationships, indicating stronger assortative preferences for height in a long-term context. These results provide preliminary evidence that, in addition to mate preferences for other physical traits related to mate quality such as masculinity in the body, face, and voice, assortative preferences for height do vary as a function of expected relationship length, but this was surprisingly only observed for female height.